Trabalhadores com ensino superior: Área de formaç\~ao, ocupaç\~ao e diferencial de rendimentos em relaç\~ao aos trabalhadores com ensino médio - Maurício Cortez Reis (Instituto de Pesquisa Econômica Aplicada (IPEA), 2023)
– This paper seeks to analyze labor earnings differences between workers with bachelor's degree and those with secondary education taking into account the heterogeneity across fields of study in the former group. Labor earnings differentials are decomposed to quantify the contribution of three main factors associated with tertiary education: general skill acquired in the program, access to higher-paying occupations, and the match between skills acquired and occupation requirements. According to the results, those three elements play important roles. Evidence also indicates that individuals with a bachelor's degree, whatever their fields of study, have larger labor earnings than lower educated ones, on average, even when their occupations do not require higher education and are weakly related to skills acquired during tertiary studies.
10419/284917
Keywords: J24; J31; I23; I26; 330; tertiary education; fields of study; occupation; labor earnings